Restitution for a failure of condition - Pilkington, T (2023)
This thesis examines the justification for restitutionary awards for a failure of condition and considers when, given this justification, such awards should be made. It is argued that restitutionary awards for a failure of condition give effect to, but do not enforce, an agreement between the parties. As to when such awards should be made, it is argued that restitution for a failure of condition should generally be awarded where C and D agreed that D’s entitlement against C to a payment made by C to D, a performance of a service by C for D, or transfer of a right from C to D remained subject to a condition and that condition has failed. It is further demonstrated that where D’s entitlement against C to the transfer of a right was subject to a condition that has now failed, D may come under a restitutionary duty to transfer a right to C, which a court may specifically enforce.